KINERJA BHAYANGKARA PEMBINA KEAMANAN DAN KETERTIBAN MASYARAKAT (BHABINKAMTIBMAS) DI KELURAHAN TANJUNG AGUNG KECAMATAN BATURAJA BARAT KABUPATEN OGAN KOMERING ULU - Eva Susanti (Universitas Bandar Lampung (UBL), 2019)
At present the main problem in the implementation of Security and Order Development is human resources. The pattern of multiple positions in the Police has led to the formation of guidance not optimal even though both in terms of work productivity and service quality but from the side of responsiveness and responsibility and accountability is still not optimal. This study aims to determine the performance of Bhayangkara Pembina Masyarakat Security and Order in creating security and order in the community. In this study the authors used qualitative research methods with a descriptive approach. The performance of Bhabinkamtibmas in Tanjung Agung Subdistrict, West Baturaja Subdistrict in fostering community security and order has run according to what is expected and running well, both from the police as the duty bearer of Bhabinkamtibmas and from the government and the community itself although there is still a lot to be improved.